1995
DOI: 10.1002/polb.1995.090331708
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between gas permeation and free‐volume hole properties probed by positron annihilation spectroscopy

Abstract: Free‐volume hole sizes, fractions, and distributions in a series of polycarbonate‐based polymers are measured by using positron annihilation lifetime (PAL) spectroscopy. Correlations between the obtained free‐volume hole properties and gas diffusion coefficients are observed. © 1995 John Wiley & Sons, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
90
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(98 citation statements)
references
References 24 publications
7
90
1
Order By: Relevance
“…The most thorough study of this kind yet conducted was carried out by Shantarovich and co-workers where positron lifetime spectra were collected for 10 glassy polymers (233). Jean and colleagues used PALS to study the same PC s shown in 26 PC, TMPC, HFPC, and TMHFPC (227). The distribution of free-volume hole sizes in these polymers is given in Figure 40 along with the molecular volume of common penetrants.…”
Section: Additional Characterization Techniquesmentioning
confidence: 97%
See 1 more Smart Citation
“…The most thorough study of this kind yet conducted was carried out by Shantarovich and co-workers where positron lifetime spectra were collected for 10 glassy polymers (233). Jean and colleagues used PALS to study the same PC s shown in 26 PC, TMPC, HFPC, and TMHFPC (227). The distribution of free-volume hole sizes in these polymers is given in Figure 40 along with the molecular volume of common penetrants.…”
Section: Additional Characterization Techniquesmentioning
confidence: 97%
“…A detailed description of equation 82 is given elsewhere (228). Because PALS is still a new technique for characterizing glassy polymers, only a limited number of materials have been investigated, which are also of interest from a gas transport standpoint (227,(229)(230)(231)(232)(233)(234). The most thorough study of this kind yet conducted was carried out by Shantarovich and co-workers where positron lifetime spectra were collected for 10 glassy polymers (233).…”
Section: Additional Characterization Techniquesmentioning
confidence: 99%
“…It is quite difficult with the higher fraction of mobile components found for PET in the mid-KHz region. to explain this behavior on the basis of static theories 19,20 which invoke free volume as a determinEvaluating the details of the motion, the terephthalic ring flip alone doesn't seems to provide ing factor in gas permeation. Both PEN and PET crystallize very fast and have a high T g , therefore a sufficient vent to the passage of gas molecules.…”
Section: Proton T 1r Measurementsmentioning
confidence: 99%
“…37 In our previous PAS results we found a correlation between gas permeability and the observed fraction of free volume. 38 Existing positron lifetime studies in sorption of CO 2 in a series of polyimides show correlation between hole volumes and diffusion properties of exposed gases. 39,40 The microstructure changes due to different gas exposure in polycarbonatebased polymers have been observed by using PAS.…”
Section: Introductionmentioning
confidence: 98%